Sudden death after ethyl alcohol intoxication in chronic alcoholics: two case reports - Zorica Bozhinoska; Ana Ivcheva; Zlatko Jakovski; Marija Bujarovska Petrovikj; Zoran Zhivikj; Tanja Petreska Ivanovska; Aleksandar Stankov (Makedonsko Farmacevtski Bilten)
Chronic alcohol consumption represents a significant social and public health concern, as it is associated with an elevated risk of sudden death. Examination of the bodies of individuals who were known to be chronic drinkers and died suddenly is common in the forensic pathology settings. The primary causes of mortality in chronic alcoholics include liver and cardiac dysfunction; however, metabolic disturbances such as alcoholic ketoacidosis and acute alcohol intoxication can be also important contributors. This paper presents two cases of sudden death in individuals with a history of chronic alcohol abuse. Based on autopsy and histopathology findings, along the results from toxicological examinations, the deaths of two chronic alcoholics were certified to acute alcohol intoxication. This highlights the complex relationship between tolerance, intoxication, and the increased vulnerability of chronic drinkers, making it an important subject for further study in forensic pathology.